A CONCEPÇÃO DE JUVENTUDE NA AGENDA PÚBLICA NO BRASIL NOS ANOS DE 2011 A 2013 - Schultz, Elisa Stroberg (2013)
This research aims to contribute to the discussions on the various conceptions or youths found on the public agenda of Brazil in the years 2010-2012. The relationships between youth and public agenda were raised from their own data policies / programs or actions available on the websites of 24 (twenty four) of the Brazilian Government Ministries, of nine (09) Secretaries of the Presidency with status of Ministry and six (06) Agencies with status of Ministry of Government Dilma. The research used the method social historical, with a survey and analysis of the data and with a theoretical and methodological framework. Both the historical process as the sociological, anthropological, legal, among others, recognizes the importance of youth in the history of the world, breaking many of the precepts. The text is divided into three chapters. The first chapter discusses a history of youth in Brazil until his appreciation today. The second chapter presents the research itself and the great divergence between the various conceptions of youth in the areas surveyed. The third chapter presents an analysis of the search about the concept that has been understood and applied by the National Public Agenda, which is consistent with the policy in order to meet demand, or at least part of it. Thus, it was possible to understand the youth or youths in Brazil in different concepts used in the policies presented.